Investigation of the effect of Pilates combined exercise program with mat and equipment on fatigue and physical self-perception in sedentary women: A randomized controlled study - Dicle Sarıtaş; Pelin Pişirici (Turkish Journal of Kinesiology)
In this study, the effect of the combination of mat and equipment-based Pilates exercise method applied to sedentary female individuals on fatigue and physical self-perception was examined. 70 women between the ages of 18 and 45, defined as sedentary according to the International Physical Activity Questionnaire, were included in the study. Participants were randomized into combined Pilates exercise (PG=35) and control (CG=35) groups. Pilates exercises were given three days a week, 50 minutes each session, for 10 weeks. No intervention was made to CG. Fatigue Severity Scale and Physical Self Inventory evaluations were repeated for pre- and post-intervention (10th week). The initial data of the participants showed a homogeneous distribution. In the results, in intragroup comparison, a statistically significant improvement in fatigue severity (p=0.001; p